Crisis management in late antiquity (410-590 CE) : a survey of the evidence from episcopal letters - Allen, Pauline, 1948- (Vigiliae Christianae, Supplements, 2013)
Pauline Allen and Bronwen Neil investigate crisis management as conducted by the increasingly important episcopal class in the 5th and 6th centuries. Their basic source is the neglected corpus of bishops' letters in Greek and Latin, the letter being the most significant mode of communication and information-transfer in the period from 410 to 590 CE. The volume brings together into a wider setting a wealth of previous international research on episcopal strategies for dealing with crises of various kinds. Six broad categories of crisis are identified and analysed: population displacement, natural disasters, religious disputes and religious violence, social abuses and the breakdown of the structures of dependence. Individual case-studies of episcopal management are provided for each of these categories. This is the first comprehensive treatment of crisis management in the late-antique world, and the first survey of episcopal letter-writing across the later Roman empire.